Administrative Responsibility for Offenses in Economic Areas - M. N. Kobzar-Frolova (Сибирское юридическое обозрение, 2019)
Relations in economic areas is a special sphere of social relations, which is associated with the phenomenon of ownership and which are regulated by civil, budget, tax, customs legislation and others. The federal laws on budgetary, tax, and customs relations adopted at the turn of the 20th-21st centuries enshrined the corresponding types of responsibility that operated in parallel with the administrative one. The variety of types of responsibility for offenses in economic areas made it difficult for law enforcement practice. The work analyze the basis of responsibility in economic areas, to explore the legal nature of liability for violation of legislation on taxes and fees and show its similarity to the legal nature of administrative responsibility. It is proved that the only type of responsibility for offenses in economic areas (in the field of finance, budget, taxes, customs, banking, etc.) is administrative responsibility. Identified the legal nature of liability for violations of legislation on taxes and fees. A proposal was made to remove from the Tax Code of the Russian Federation norms on liability for violations of legislation on taxes and fees and to introduce Chapter 15.1 into the Code of the Russian Federation on Administrative Offenses, and at the same time to remove the elements of violation of legislation on taxes and fees from Chapter 15.1 of the Code of the Russian Federation on Administrative Offences.